Current Knowledge on the Role of Cardiolipin Remodeling in the Context of Lipid Oxidation and Barth Syndrome - Liang, Zhuqing; Schmidtke, Michael W.; Greenberg, Miriam L. (Frontiers in Molecular Biosciences, 2022)
Barth syndrome (BTHS, OMIM 302060) is a genetic disorder caused by variants of the TAFAZZIN gene (G 4.5, OMIM 300394). This debilitating disorder is characterized by cardio- and skeletal myopathy, exercise intolerance, and neutropenia. TAFAZZIN is a transacylase that catalyzes the second step in the cardiolipin (CL) remodeling pathway, preferentially converting saturated CL species into unsaturated CLs that are susceptible to oxidation. As a hallmark mitochondrial membrane lipid, CL has been shown to be essential in a myriad of pathways, including oxidative phosphorylation, the electron transport chain, intermediary metabolism, and intrinsic apoptosis. The pathological severity of BTHS varies substantially from one patient to another, even in individuals bearing the same TAFAZZIN variant. The physiological modifier(s) leading to this disparity, along with the exact molecular mechanism linking CL to the various pathologies, remain largely unknown. Elevated levels of reactive oxygen species (ROS) have been identified in numerous BTHS models, ranging from yeast to human cell lines, suggesting that cellular ROS accumulation may participate in the pathogenesis of BTHS. Although the exact mechanism of how oxidative stress leads to pathogenesis is unknown, it is likely that CL oxidation plays an important role. In this review, we outline what is known about CL oxidation and provide a new perspective linking the functional relevance of CL remodeling and oxidation to ROS mitigation in the context of BTHS.